Robustness and evolvability in the functional anatomy of a PER-ARNT-SIM (PAS) domain - Philip, Andrew F. (National Academy of Sciences, 2010)
The robustness of proteins against point mutations implies that only a small subset of residues determines functional properties. We test this prediction using photoactive yellow protein (PYP), a 125-residue prototype of the PER-ARNT-SIM (PAS) domain superfamily of signaling proteins. PAS domains are defined by a small number of conserved residues of unknown function. We report high-throughput biophysical measurements on a complete Ala scan set of purified PYP mutants. The dataset of 1,193 values on active site properties, functional kinetics, stability, and production level reveals that 124 mutants retain the characteristic photocycle of PYP, but that the majority of substitutions significantly alter functional properties. Only 35% of substitutions that strongly affect function are located at the active site. Unexpectedly, most PAS-conserved residues are required for maintaining protein production. PAS domain activation often involves conformational changes in α-helices linked to the PAS core. However, the mechanism of transmission and kinetic regulation of allosteric structural changes from the PAS domain to these helices is not clear. The Ala scan data reveal interactions governing allosteric switching in PYP. The photocycle kinetics is significantly altered by substitutions at 58 positions and spans a 3,000-fold range. Nine residues that dock the N-terminal α-helices of PYP to its PAS core regulate signaling kinetics. Ile39 and Asn43 are identified as part of a mechanism for regulating allosteric switching that is conserved among PAS domains. These results show that PYP combines robustness with a high degree of evolvability and imply production level as an important factor in protein evolution.